The Miners and the Mounties: The Royal North West Mounted Police and the 1906 Lethbridge Strike - Baker, William M. (Labour / Le Travail, 1991)
This essay explores the nature of the relationship between police and workers using the 1906 strike of Lethbridge coalminers as a case study. Following a discussion of relevant literature and theoretical frameworks it examines in detail the relationship between the Lethbridge strikers and the Mounted Police. This interaction was extremely complex with each party having an influence on the other. Consequently, no definitive conclusion can be drawn as to the interpretative debate between pluralist theory and class cortflict theory insofar as police-striker relations are concerned.
Keywords: COAL mines & mining; CRIMINAL justice administration; CRIMINAL justice personnel; Coal miners; DEMONSTRATIONS (Collective behavior); LETHBRIDGE (Ont.); Labor disputes; Legal status; laws; etc.; Ontario; PEACE officers; STRIKES & lockouts